Inequality and guard labor, or prohibition and guard labor? - Vincent Geloso; Vadim Kufenko (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2017)
In this paper, we consider whether or not inequality forces society to expend more resources on supervision which imposes an extra cost to doing business. Some argue that since inequality deteriorates social capital, there is a greater need for supervisory labor which is a costly burden to bear. We propose an alternative (but not mutually exclusive) explanation. We argue that the war on drugs leads to institutional decay and lower levels of trust which, in turn, force private actors to deploy resources to supervise workers and protect themselves. Our explanation complements the argument regarding the link between inequality and guard labor.
urn:nbn:de:bsz:100-opus-13378
Keywords: N11; N21; E31; 330; Economic Growth; Inequality; Drugs; Guard Labor